The Effect of Different Stimulation Rates on Brainstem Auditory-Evoked-Potential Responses - Andrade, Kelly Cristina Lira de; Frizzo, Ana Cláudia Figueiredo; Oliveira, Katielle Menezes de; Pinheiro, Natália dos Santos; Marques, Maria Cecilia dos Santos; Carnaúba, Aline Tenório Lins; Costa, Klinger Vagner Teixeira; Menezes, Pedro de Lemos (International Archives of Otorhinolaryngology, 2023)
Introduction Auditory-evoked potentials are influenced by several factors, including polarity, filter, stimulus intensity and stimulation rate. The presentation of higher rates of stimuli per second enables the collection of a greater number of responses in a given period of time, promoting a shorter testing time; however, the collected recordings are subject to changes related to wave morphology.Objectives To compare the brainstem auditory-evoked-potential responses with click stimulus with the most commonly used stimulation rates in the clinical practice.Methods The present cross-sectional analytical study was performed with fifteen participants of both genders and normal hearing thresholds. The brainstem auditory-evoked potential was performed at four different stimulation rates (21.1, 26.7, and 27.7 stimuli/s, and a rate determined based on a mathematical calculation using the a measurement of the transmission frequency of the power grid at the time of the examination).Results We observed that the rate of 21.1 stimuli/s showed the highest amplitudes for waves I, III, and V when compared with the other rates. The rate of 26.7 stimuli/s, when compared with 27.7 stimuli/s, showed a higher amplitude for wave V. The latency if wave V was significantly lower with the rate of 21.1 stimuli/s than with 27.7 stimuli/s.Conclusions The stimulation rate interferes with wave latencies and amplitudes; its decrease from 27.7 to 21.1 stimuli/s decreases the latency of wave V and increases the amplitues and improves the morphology of waves I, III and V. In addition, we found evidence that suggests an improvement in the visualization of wave III by adjusting the stimulation rate based on a measurement of the local transmission frequency of the power grid.
Keywords: hearing; electrophysiology; evoked potentials